Drinking water and hygiene and its relation to COVID-19 mortality and dissemination - Mora-Alvarado, Darner A. (2022)
The present study analyses data from the WHO/UNICEF Joint Monitoring Programme for Water Supply, Sanitation and Hygiene (JMP) service ladders for drinking water and hygiene. The aim is to establish whether or not there is a correlation between these indicators and their relation to COVID-19 dissemination and mortality until 06/07/2020. The data form the report called ‘Progress on Drinking Water, Sanitation and Hygiene 2017’ was analysed. The results showed a relation between drinking water and hygiene shortage and the coronavirus dissemination. A Peruvian study compared the COVID-19 situation within countries in Latin America that provided data, i. e. Mexico, Guatemala, Costa Rica y Ecuador, only 20 countries (9,6%) reported data worldwide. Drinking water values reported were lower than hygiene values in several countries. This suggests that a proportion of the population use non-potable drinking water for their hygiene, which boosts pathogens dissemination. Therefore, it is recommended to promote potable drinking water, sanitation and hygiene coverage in every country, in order to improve public health.